Care for younger people with dementia during the progression of the disease: Care promoting quality of life? - Thorsen, Kirsten; Johannessen, Aud (Nordisk Tidsskrift for Helseforskning, 2021)
Younger people with dementia (YOD) (< 65 years) have other life experiences and needs than elderly people with dementia. Adequate help in early stages may be of little use later. Younger people with dementia living alone will be especially vulnerable when public help is insufficient or not adapted to their needs. This article exposes and discusses experiences and needs in different stages of dementia from a narrative longitudinal study over five years with ten participants with YOD living alone, focusing on the last stages. The narrative of Elsa will elaborate her reactions with YOD during the development of dementia. At home Elsa sensed anxiety, depression and loneliness. After moving into a well-organized nursing home, she experienced vitalization, community and sense of meaning. In later stages of dementia, she experienced increasing distance to the other residents and social isolation. She felt neglected by the personnel – “not seen” and validated. She lacks identity-support. During all stages of dementia, health personnel must validate people with YOD and provide person-centered care and identity support.
Keywords: Early-onset dementia; care; progression of dementia; last stages; validation; identity support